PENDAMPINGAN SISWA SMK ISLAMIC CENTRE BAITURRAHMAN SEMARANG DALAM PENINGKATAN MOTIVASI DAN STRATEGI PEMILIHAN PROGRAM STUDI PADA PERGURUAN TINGGI - Nugroho, Kristiawan; Setiawan, Mulyo Budi; Mulyani, Sri; Nugroho, Isworo (Fakultas Teknologi Informasi dan Industri Unisbank, 2023)
This community service activity aims to provide assistance to provide motivation and understanding of further studies at tertiary institutions at the Baiturrahman Islamic Center Vocational School, Semarang. This was done in order to support students' design creativity. In the initial discussions that were conducted, it was seen that knowledge regarding further studies in tertiary institutions was still lacking. Activities carried out in the form of interactive presentations and questions and answers with students regarding their desire to continue their education to the tertiary level. This activity is expected to provide education about the importance of determining the right strategy in choosing majors and tertiary institutions so that students can choose the right majors according to their wishes to continue their education to the tertiary level as a means of achieving their goals in the future.